A quarter century of gender and information systems research: the role of theory in investigating the gender imbalance. (2nd January 2021) - Mennega, Nita; de Villiers, Carina
Abstract: This study analyses the role of theory in gender and information systems (IS) research by providing a descriptive review of 25 years of IS journal publications on the topic of gender and IS. Trauth performed a critical literature analysis on research papers that appeared in information systems journals between 1992 and 2013. This paper extends the analysis by Trauth adding a literature analysis for research papers from 2012 to 2020. Decades of research on the under-representation of women in information systems (IS) has revealed a checkered landscape of studies ranging from completely atheoretical to theoretically well-informed work. Contained in this considerable body of knowledge is a collection of explicitly theorized gender and IS studies. These are the only types of study that allow researchers to build upon each other's work, and allow the field to progress from purely descriptive studies to studies that are more analytical in nature, with the goal of suggesting interventions aimed at broadening participation in the IT workforce. This study examines only explicitly theorized research and finds that IS research has indeed progressed from gender essentialist studies toward gender intersectional studies. The intersectional approach encourages explanatory studies that investigate relevant issues in today's diverse global IT workforce and allows the identification of suitable interventions.